Pelatihan Pembuatan Business Plan dan Digital Marketing bagi Pelaku UMKM di Desa Jayagiri Kecamatan Lembang - Kusmana, Agus; Ali, Syarif (Batara Wisnu : Indonesian Journal of Community Services, 2022)
Bojong Cae Village, Cibadak District is located in the government area of ??Lebak Banten Regency. Most of the residents in Bojong Cae Village work as laborers, entrepreneurs, employees and farming. For potential commodities in this area, there are several home industries as well as in the agro-business sector. One of the agricultural commodities found in this area is melinjo fruit and used as chips. The problem faced is that there are still many housewives in the area who do not have jobs that can provide additional income for their families. Making business plans and on-line marketing provides insights and business opportunities for PKK mothers and MSMEs. The specific targets of this service activity are (1) providing an understanding of on-line business planning and marketing; (2) partners are able to make good business plans; (3) partners are able to implement on-line marketing; (4) Creating a productive society and having additional income to support the family economy. The methods used in the on-line business planning and marketing training are (1) counseling / outreach; (2) training in business planning; (3) on-line marketing training; (4) monitoring and assistance